EXTRACTION, ISOLATION AND STRUCTURAL ELUCIDATION OF FLAVONOID FROM CHROZOPHORA PLICATA LEAVES AND EVALUATION OF ITS ANTIOXIDATIVE POTENTIALS - Kumar, Kadiri Sunil; Rao, Avanapu Srinivasa (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This investigation involves the extraction, isolation, and characterization of flavonoid from a Euphorbiaceae family plant Chrozophora plicata followed by evaluation of its antioxidant principles. Methods: The dried leaves were subjected to sequential soxhlation with polar and nonpolar solvents. Methanolic extract reveals the presence of large amount of flavonoids. Methanolic extract was subjected to isolation using column chromatographic analysis with solvents such as petroleum ether, chloroform, hexane, ethyl acetate, methanol, and water. Further, the isolated compound was subjected to thin layer chromatography technique and spectral analysis such as infrared, 1HNMR, 13CNMR, mass spectroscopy, and high performance thin layer chromatography (HPTLC) finger printing techniques. The compound was evaluated for in vitro antioxidant studies using 2,2-diphenyl-1-picrylhydrazyl (DPPH), NO assay, reducing power assay, H2O2 scavenging assay, superoxide anion scavenging assay and Î²-Carotene linoleate system and in vivo antioxidative studies using carbon tetrachloride (CCl4), and acetaminophen intoxicated rats. Results: The compound was isolated in methanol:water in the ratio of 80:20 using column chromatographic technique. On the basis of phytochemical, chromatographic, and spectral analysis, the isolated compound was identified as kaempferol and finally with HPTLC finger printing technique it was found that the Rf value of the isolated compound was found to be 0.58 which is nearly similar to the Rf value of standard kaempferol (0.55). Hence, the isolated compound was confirmed as kaempferol and is structurally elucidated as 3,5,7-trihydroxy-2-(4-hydroxyphenyl)chromen-4-one. This compound was isolated for the first time from the C. plicata leaves. The in vitro antioxidant assay of isolated flavonoid has shown a dose-dependent increase in free radical scavenging activity using DPPH, no assay, reducing power assay, H2O2 scavenging assay, superoxide anion scavenging assay, and Î²-carotene linoleate system. Further, the methanolic extract of C. plicata (MECP) leaves was subjected to single dose acute toxicity study for 14 days in female rats on the basis of OECD guidelines 423 and the therapeutically selected doses were 200 mg/kg and 400 mg/kg. In vivo antioxidant studies in CCl4 and acetaminophen intoxicated rats indicated that the MECP leaves have significantly decreased lipid peroxidation in a dose-dependent manner and increased the levels of catalase, superoxide dismutase, and glutathione. Conclusions: By the above results, it was concluded that the isolated compound from C. plicata leaves was confirmed as kaempferol and it possesses significant antioxidative potentials. Keywords: Chrozophora plicata leaves, Flavonoids, Extraction, Isolation, Characterization, Methanolic extract, Antioxidant activity, Carbon tetrachloride, Acetaminophen.